The Relationship between the Clean and Healty Living Behavior Implementation and Stunting Prevalence Amid The Covid-19 Pandemic - Nurbaety Nurbaety; Tri Yubiah; Nurlaili Zulkaidah (Science Midwifery, 2022)
Stunting is a chronic nutritional problem that remains unresolved in Indonesia, in which Indonesia ranked third in stunting prevalence in the Southeast Asia region, reaching to 36.4%. During the COVID-19 pandemic, stunting prevalence can be decreased by implementing the clean and healthy living behavior. Unfortunately, community’s awareness regarding the importance of the clean and healthy living behaviors is lacking. The results of a survey done to 5 mothers of toddlers aged 12-59 months showed that they washed their hand improperly. They often washed their hands before and after eating only using water without soap, not washing their hands before breastfeeding, and not using running water. This study examined the relationship between the clean and healthy living behavior implementation in the household with stunting prevalence during the COVID-19 pandemic at Bolo Health Center. This quantitative research was performed using a cross sectional design, involving 71 randomly-selected mothers of toddlers at the Bolo Health Center. Data were analyzed using Chi-square test, which results exhibited the importance of the clean and healthy living behavior in relation to the stunting prevalence in toddlers amidst the COVID-19 pandemic. The statistical analysis resulted in a correlation coefficient value of 0.310 and a confidence alpha value of 0.033. These values indicated the presence of a relationship between the two variables. Proper implementation of the clean and healthy living behavior is expected to decrease the stunting prevalence in toddlers. Toddlers are expected to grow and thrive as strong and quality future generation of the nation..